ANALISIS EFEKTIVITAS SISTEM RUJUKAN MATERNAL VERSI INDRAMAYU (SI-IRMA-Ayu) DALAM MEWUJUDKAN SISTEM RUJUKAN MATERNAL YANG EFEKTIF DI KABUPATEN INDRAMAYU - Setyo Dwi Widyastuti; Yadi Hidayat; Rita Meilawati (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2022)
The low quality of the referral system is one factor to high maternal mortality rate. It is necessary for an effective referral system, in which there is good coordination between the components involved in maternal health care. In Indramayu district has created a referral system that is based on information technology. Namely Referral Information System for Maternal and Neonatal Version Indramayu (Si-IRMA-Ayu). Si-IRMA-Ayu is an information and communication systems based on information technology for pregnant women, health workers and health facilities in the process of pregnancy, birth plans, prevention of complications, and referral of maternal and neonatal emergencies that aims to save the lives of mothers and babies. The purpose of this study to determine the effectiveness of Maternal Referral System Version Indramayu (Si-IRMA-Ayu) in creating an effective maternal referral system in Indramayu. Method of research using qualitative method with case study approach. Informants in this study amounted to 15 informants who are in the working area of Indramayu District Health Office, Health Center Haurgeulis, Patrol, Cikedung, Lelea, Krangkeng, Plumbon and Indramayu Hospital. Sampling technique used is purposive sampling. The process of data analysis was done using qualitative data analysis model of Miles and Huberman. The results showed that the Maternal Referral Information System Version Indramayu (Si-IRMA-Ayu) has become an effective referral in Indramayu. Referral system maternal version of Indramayu (Si-IRMA-Ayu) quite effectively become a referral system that is effective in Indrmayu and to further improve the effectiveness of the referral system, the Department of Health needs to improve facilities throughout the hospital in Indramayu, cooperation with hospitals outside Indramayu more reproduced and increase the number of obstetricians in particular in the western district of Indramayu.